1984 ネン アイスランド ニ オケル オーロラ ゲンショウ ノ キョウヤク テン カンソク ホウコク - 佐藤, 夏雄; サトウ, ナツオ; 藤井, 良一; フジイ, リョウイチ; 国分, 征; コクブン, ススム; 荒木, 喬; アラキ, タカシ; Saemundsson, Th.; Sato, Natsuo; Fujii, Ryoichi; Kokubun, Susumu; et al. (1985)
P(論文) 南極の昭和基地, みずほ基地, マラジョージナヤ基地の地磁気共役点であるアイスランドのHusafell, Isafjordur, Tjornesの3点において, オーロラ現象の共役性を解明するための観測計画が昭和58年度より開始された。59年度は既に予備調査したIsafordur, Tjornesに本格的な観測装置を設置した。1984年9月2日より, 既設のHusafell観測所を含め, 3ヵ所でオーロラ現象の同時連続観測を開始した。今回の滞在中, 約4夜におよぶ南極との可視オーロラの同時観測に成功した。 This campaign has been organized by the National Institute of Polar Research as a cooperative project with the Science Institute, University of Iceland. This campaign aims at a further understanding of physical processes in auroras by a coordinated observation of magnetic field variations, magnetic ULF waves, ELF-VLF emissions, cosmic noise absorption, and spatial and temporal variations of auroras in the geomagnetically conjugate polar regions. With the data recorded at the three conjugate station pairs Syowa-Husafell, Mizuho-Isafjordur, and Molodezhnaya-Tjornes, we investigate the temporal and spatial conjugacy of both auroras and wave phenomena associated with auroral particle precipitation. Then we study the auroral particle acceleration process in the ionosphere-magnetosphere energy coupling system and also the generation and propagation mechanisms of ULF, ELF and VLF plasma waves. Four Japanese scientists have been in Iceland from August 13 to October 7,1984. Fluxgate magnetometer, search coil magnetometer, riometer, ELF/VLF wave receiver, photometer, and analogue and digital data recorders were set up at Isafjordur (66.1°N, 23.1°W) and Tjornes (66.2°N, 17.1°W) in August 1984. Simultaneous observations at three stations in Iceland including Husafell (64.7°N, 21.0°W), where most of instruments had been constructed in 1983,started from September 2,1984 corresponding to the conjugate observations in Antarctica. During their stay in Iceland, visible auroral data have been obtained simultaneously at conjugate-pair stations at four nights. departmental bulletin paper